Radiation mechanism on dissipative ternary hybrid nanoliquid flow through rotating disk encountered by Hall currents: HAM solution - M.D. Shamshuddin; Nevzat Akkurt; Anwar Saeed; Poom Kumam (Alexandria Engineering Journal, 2023)
The energy transition to enhance heat transport during the flow of ternary hybrid nanofluid comprised of Copper (Cu), Iron oxide (Fe3O4), Silicon dioxide (SiO2) nanoparticles and Polymer as base liquid over a revolving disk surface has been reported. From the several existing techniques, adding nanoparticles to standard working fluids is an effective approach that might dramatically improve the rate of heat transfer. The Hall and radiation impacts are also considered. A mathematical model is developed by assuming the flow as incompressible and purely radial in a cylindrical coordinate system and appropriate similarity variables are introduced for problem simplification and dimensionless analysis. The solution of complex generated PDEs was calculated using semi analytical method known as Homotopy Analysis Method (HAM) after translating them into corresponding ODEs. It has been observed that the consequences of thermal radiation, dissipation term, unsteadiness and rotation parameters boost the energy transmission rate and enhances the heat transfer rate of tri hybrid nanofluids. However, Cu-Fe3O4 nanoparticles in the base fluid remarkably magnifies the energy transmission rate. The unitary ternary hybrid nanofluid (Cu, Fe3O4, SiO2) has higher velocity profiles as compared to unitary nano fluid (Cu) and hybrid nano-fluid (Cu-Fe3O4).